Exploring children’s cultural perceptions through tasks based on films in an afterschool program - Mojica, Claudia (Colombian Applied Linguistics Journal, 2007)
This is a report on a finished research project that explores the cultural perceptions of children through tasks based on films in an English after-school program. This qualitative case study was carried out at a private school in Bogotá and it fostered students´ active participation in the development of the classes and explored their cultural perceptions. The data collected revealed that this process of construction of the concept of culture was built by the learners from the different types of knowledge about the world, the practices, and the artifacts embedded in the community. As for the cultural perceptions that emerged in the data, these corresponded to the interpretations of students’ world and life experience.